Accidental removal of dialysis central venous catheters: 9-year experience and prevention strategies in a Japanese community hospital - Soki Urushibara; Akemi Hara; Hirose Nakamoto; Haruhisa Ozawa; Yuki Nemoto; Shun Watanabe; Ryo Ohata; Takuto Sakai; Toyoaki Sawano; Akihiko Ozaki; Tomohiro Kurokawa; Masayuki Okazaki; et al. (Renal Replacement Therapy)
Abstract Background Accidental removal of dialysis central venous catheters is a potentially life-threatening complication in hemodialysis patients. This study investigated the incidence, risk factors, and outcomes of accidental catheter removal in a community hospital setting. Methods We conducted a retrospective analysis of patients who received dialysis central venous catheter insertions at our community hospital in Fukushima, Japan, from January 2015 to December 2023. We evaluated catheter insertions and removals; reviewed patient characteristics, catheter specifications, and clinical outcomes; and assessed the effectiveness of safety protocols implemented during the study period. Results We identified 2456 catheter insertions and 40 removal events (1.6%) among 39 patients (median age 81 years, 51.4% female). Cognitive impairment was present in 75.0% of documented cases. The overall removal rate was 1.5%, with higher rates in non-cuffed catheters (1.7%) than cuffed catheters (1.0%). Insertion sites included internal jugular (62.2%), femoral (35.1%), and subclavian (2.7%). Three fatal cases occurred with femoral catheters between 2016 and 2017, all during nighttime. No fatalities occurred after implementing comprehensive safety measures in 2020. Conclusions In this community hospital, accidental catheter removal occurred at a rate of 1.5%, with potentially fatal outcomes particularly among patients with femoral catheters. Comprehensive safety measures effectively prevented fatal events, although non-fatal removals persisted.